2016
DOI: 10.1007/s00894-016-3070-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the hydrogen-bonding motif in the melamine–cyanuric acid co-crystal: a topological study

Abstract: The melamine (M)/cyanuric acid (CA) supramolecular system is perhaps one of the most exploited in the field of self-assembly because of the high complementarity of the components. However, it is necessary to investigate further the factors involved in the assembly process. In this study, we analyzed a set of 13 M n /CA m clusters (with n , m = 1, 2, 3), taken from crystallographic data, to characterize the nature of the hydrogen bonds involved in the self-assembly of these components as well as to provide grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In particular, the two unmodified faces of these molecules enable the formation of assemblies named “rosette”, “linear tape”, and “crinkled tape” (Figure ). ,, The two tape assemblies remain unbounded in one dimension and therefore are potentially of infinite length, making them attractive for extended assemblies. ,, The hexad rosette structure, on the other hand, being restricted to six monomers in a specific planar arrangement, is attractive for the rational design of supramolecular assemblies. , After decades of research on these pairing systems, the only reported crystal structure for stacked hexameric rosettes containing one of these triamino species paired with a triketo species is of two stacked MA–BA hexads with bulky substituents attached to each heterocycle. It is likely that the bulky substituents prevent extended stacking of hexads and cause the observed deformation of the hexad planar geometry …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the two unmodified faces of these molecules enable the formation of assemblies named “rosette”, “linear tape”, and “crinkled tape” (Figure ). ,, The two tape assemblies remain unbounded in one dimension and therefore are potentially of infinite length, making them attractive for extended assemblies. ,, The hexad rosette structure, on the other hand, being restricted to six monomers in a specific planar arrangement, is attractive for the rational design of supramolecular assemblies. , After decades of research on these pairing systems, the only reported crystal structure for stacked hexameric rosettes containing one of these triamino species paired with a triketo species is of two stacked MA–BA hexads with bulky substituents attached to each heterocycle. It is likely that the bulky substituents prevent extended stacking of hexads and cause the observed deformation of the hexad planar geometry …”
Section: Introductionmentioning
confidence: 99%
“…1,2,4−16 The two tape assemblies remain unbounded in one dimension and therefore are potentially of infinite length, making them attractive for extended assemblies. 6,9,16 The hexad rosette structure, on the other hand, being restricted to six monomers in a specific planar arrangement, 17 is attractive for the rational design of supramolecular assemblies. 14−16,18−21 After decades of research on these pairing systems, the only reported crystal structure for stacked hexameric rosettes containing one of these triamino species paired with a triketo species is of two stacked MA−BA hexads with bulky substituents attached to each heterocycle.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The M-CA system is a classical example of molecular self-assembly governed by strong hydrogen bonding and soft π–π interactions (aromatic stacking). The results of the density functional theory (DFT) studies , confirm that high stability of the macroscale M-CA crystals is a result of the large number of intermolecular hydrogen bonds formed between M and CA (Figure ), among which N–H···N bonds are almost two times stronger than N–H···O . The most energetically favorable structures are rosette-like patterns, linear tapes, and their combinations .…”
Section: Introductionmentioning
confidence: 76%
“…The results of the density functional theory (DFT) studies 2,15−18 confirm that high stability of the macroscale M-CA crystals is a result of the large number of intermolecular hydrogen bonds formed between M and CA (Figure 1), among which N−H•••N bonds are almost two times stronger than N−H•••O. 15 The most energetically favorable structures are rosette-like patterns, linear tapes, and their combinations. 19 In general, it is believed that precursors of M-CA nucleismall soluble molecular complexes resemble the same motifs of structural organization.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Nevertheless, when H is negative the hydrogen bonds are stronger than those with positive values. 34,47,48 The ellipticity , that measures the extent of the electron density within a plane containing the line path. In addition, it is a direct measure of the stability of a given bond, because it takes infinite large values preceding the coalescence of a ring critical point and a BCP.…”
Section: Topology Of the Cavitiesmentioning
confidence: 99%